Relationship between the frequency of autonomic dysfunction and the severity of chronic obstructive pulmonary disease - Tug, T; Terzi, SM; Yoldas, TK (Blackwell Publishing, 2005)
Objectives - The relationship between the frequency of autonomic dysfunction (AD) and the severity of chronic obstructive pulmonary disease (COPD) has not been exactly known, despite its importance in the pathogenesis of COPD. Therefore, we aimed to evaluate the relationship between the clinical stage severity of the disease and the frequency of AD in COPD patients. Methods - The frequency and type of AD were determined according to the clinical severity of 35 stable COPD patients. The results were compared between the mild and moderate-severe COPD groups. Sympathetic system (SS) was evaluated with sympathetic skin response (SSR), QT and QTc intervals (ms) analyses. Parasympathetic system was evaluated with the heart rate interval variations (RRIV). Results - For the total group, an AD was detected in 20 patients (57%), a parasympathetic dysfunction (PD) in 14 (40%), a mixed-type dysfunction in five (14%) and a sympathetic dysfunction (SD) in only one patient (3%). For the 12 mildly affected patients, there were cases of isolated SD in only one patient (8.5%), isolated PD in five (42%) and AD in six patients (50%). For the 23 moderate-severe COPD patients, mixed AD was detected in five patients (22%), isolated PD in nine (39%) and AD in 14 patients (61%). There were no significant differences between the two patient groups, neither for isolated parasympathetic and sympathetic, mixed form nor for total AD (P > 0.05). Conclusion - The results suggested that PD was dominant in patients with COPD. However, the frequencies of autonomic parasympathetic and sympathetic dysfunction did not increase significantly with the severity of COPD. The severity of hypoxemia and/or airflow limitation may not be the only unique or definite reason for AD in COPD, as there was not an exact correlation between the presence of AD and the severity of airflow limitation and hypoxemia.
Keywords: autonomic dysfunction; chronic obstructive pulmonary disease severity